Occupational coping self-efficacy explains distress and well-being in nurses beyond psychosocial job characteristics - Pisanti, Renato; van der Doef, Margot; Maes, Stan; Lombardo, Caterina; Lazzari, David; Violani, Cristiano (Frontiers in Psychology, 2015)
Aim: The main purpose of the present study was to extend the Job Demand Control Support (JDCS) model analyzing the direct and interactive role of occupational coping self-efficacy (OCSE) beliefs. Background: OCSE refers to an individual’s beliefs about their ability to cope with occupational stressors. The interplay between occupational stressors, job resources, and self-efficacy beliefs is poorly investigated. The present research attempts to address this gap. Design: Cross-sectional survey. Method: Questionnaire data from 1479 nurses (65% response) were analyzed. Hierarchical regression analyses were used to test the direct and moderating role of OCSE in conjunction with job demands (i.e., time pressure), and two job resources: job control (i.e., decision latitude and skill discretion) and social support (i.e., supervisor support and coworker support) in predicting psychological distress and well-being. Results: Our findings indicated that high demands, low job control, and low social support additively predicted the distress/well-being outcomes (job satisfaction, emotional exhaustion, depersonalization, psychological distress, and somatic complaints). Beyond the main effects, no significant interactive effects of demands, control, and support were found. OCSE accounted for an additional 1–4% of the variance in the outcomes, after controlling for the JDCS variables. In addition, the results indicate that OCSE buffers the association between low job control and the distress dimensions emotional exhaustion, depersonalization, and psychological distress. Low control was detrimental only for nurses with low OCSE. Conclusion: Our results suggest expanding the JDCS model incorporating individual characteristics such as OCSE beliefs, for predicting psychological distress and well-being. Limitations of the study and practical implications are discussed.